MORFOFONOLOGI DALAM KONSTRUKSI NOMINA BAHASA MANDAR: PERSPEKTIF MORFOLOGI GENERATIF (Morphophonology in Noun Construction of Mandarese: Generative Morphology Perspective) - Jerniati I. (SAWERIGADING, 2017)
This study aims to describe the morphophonology process of affix constructing noun of Mandar language. This research applies generative morphology theory and qualitative descriptive method with data collection techniques: observation, writing, and retrospection. The results show that the morphophonology of noun construction in Mandar language is found only in two affixes, namely pang- and confix pang-ang. The process of morphophonology occurs when the affixes are combined with the basic morpheme or the base word of the verb class or the noun class. Prefixes pang- if combined with base word class verbs or nouns by initial morphemes /g, j, d, b,/ bring up alomorph /pang-, pam, pany-/ and if combined with initial phonemic morphemes /p, c, t, k, h, l, r, q/ alomorph emerging /pap-, pac-, pat-, pak-, pah-, pal-, par-, and paq- /. As for the confix pang-ang when combined with the base word of the verb class or noun with initial phonemes /j, b, d, g, l, k, t, c, p/ and vowel /a, i, u, e, o/, the alomorphs that appear are /pany-ang, pam-ang, pan-ang, pang-ang, pas-ang, pal-ang, pak-ang, pat-ang, pac-ang, par-ang, pap-ang, paq-ang./AbstrakPenelitian ini bertujuan mendeskripsikan proses morfofonologi afiks pembentuk nomina bahasa Mandar. Penelitian ini menerapkan teori morfologi generatif dan metode deskriptif kualitatif dengan teknik pengumpulan data: observasi, pencatatan, dan retrospeksi. Hasil penelitian menunjukkan bahwa morfofonologi dalam konstruksi nomina bahasa Mandar ditemukan dua afiks, yaitu prefiks pang- dan konfiks pang-ang. Proses morfofonologi terjadi apabila afiks-afiks itu digabungkan dengan morfem dasar atau kata dasar kelas verba atau kelas nomina. Prefiks pang- jika digabungkan dengan kata dasar kelas verba atau nomina yang berfonem awal /g, j, d, b/ memunculkan alomorf /pang-, pam-, pany-,/. Jika digabungkan dengan morfem dasar yang berfonem awal /p, c, t, k, h, l, r, q/ alomorf yang muncul /pap-, pac-, pat-, pak-, pah-, pal-, par-, dan paq-/. Adapun konfiks pang-ang, apabila digabungkan dengan kata dasar kelas verba atau nomina yang berfonem awal /j, b, d, g, l, k, t, c, p/, dan vokal /a, i, u, e, o,/ alomorf yang muncul adalah /pany-ang, pam-ang, pan-ang, pang-ang, pas-ang, pal-ang, pak-ang, pat-ang, pac-ang, par-ang, pap-ang, paq-ang/.